Nannochloropsis gaditana as a Source of Novel Antitumor Compounds - Rafael, Carrasco-Reinado; Almudena, Escobar-Niño; Francisco Javier, Fernández-Acero (Recent Research Advances in Biology Vol. 10, 2021)
During the last decades, proteomics approaches has become in a fundamental tool to unravel the proteins dynamic of biological processes, being an essential technique for basic and applied research [1-4]. Diverse bioinformatic tools are required to manage and explore the huge amount of information obtained from a single proteomics experiment. To gain insight into potential applications of the identified proteins, a novel approach named "Applied Proteomics" has been developed by comparing the obtained protein information with the existing patents database. The development of massive sequencing technology and MS/MS improvements has allowed the application of proteomic of non-model microorganisms, which have been deeply described as a novel source of metabolites [5-8]. Between them, Nannochloropsis gaditana that has been pointed out as an alternative source of biomolecules [9-13]. Recently, our research group has reported the first complete proteome analysis of this microalga [14], which was analysed using the applied proteomics concept with the identification of 488 proteins with potential industrial applications. To validate our approach, we select UCA01 protein from prohibitin family. The recombinant protein showed its antitumor activity against two tumor cell lines, Caco2 (colon adenocarcinoma) and HepG-2 (hepatocellular carcinoma), proving that proteome data has been transformed into relevant biotechnological information. In summary, the framework of the European Union “Blue growth” politicies, the revalorization of microalgae biomass is crucial point. From Nannochloropsis gaditana has been developed a new tool against cancer, the protein named UCA01. This protein has selective effect inhibiting the growth of tumour cells, while does not show any effect over control cells. This approach describes the first practical approach to transform proteome information in a potential industrial application, named “applied proteomics”. It is based in a novel bio-algorism, which is able to identified proteins with potential industrial applications. From hundreds of proteins described in the proteome of N. gaditana, the bio-algorism identified over 400 proteins with potential use; one of them was selected as UCA01, “in vitro” and its potential prove it against cancer. The potential applications from this approach are unpredictable.